Changes in incidence and severity of commercial motorcycle accidents due to the use of delivery service platforms in Korea: a retrospective cohort study - Dam Moon; Jae Ho Jang; Jin Seong Cho; Jae Yeon Choi; Jae-hyug Woo; Woo Sung Choi; Sung Yeol Hyun; Seung Hwan Lee (Journal of Trauma and Injury)
Purpose Recently, a sharp increase in the use of delivery services has led to an increase in motorcycle accidents. This study aimed to identify the characteristics of the commercial motorcycle injured patients and factors related to the severity during the past 10 years. Methods Patients (15–64 years old) who visited the emergency department with commercial motorcycle accidents injury registered in the Korean Emergency Department-based Injury In-depth Surveillance (2011–2020) database, were included. All included cases were categorized into two groups according to the period: group 1 (2011–2015) and group 2 (2016–2020). General characteristics and the factors associated with severity were investigated. Results Among 8,123 emergency department visits, patients in group 1 were 3,071, and patients in group 2 were 5,052. The odds for severity were affected by patients age (odds ratio [OR], 1.008; 95% confidence interval [CI], 1.004–1.013), and overnight/morning (00:00–12:00; OR, 1.243; 95% CI, 1.091–1.415). The odds for severity were higher in head and neck injury (OR, 8.357; 95% CI, 7.410–9.424) and torso injury (OR, 4.122; 95% CI, 3.610–4.708). The odds for the severity of accidents based on excess mortality ratio-adjusted Injury Severity Score (EMR-ISS) after 2015 were significant (OR, 1.491; 95% CI, 1.318–1.687). Hospitalization in the intensive care unit and death were associated with accidents after 2015 (OR, 2.593; 95% CI, 2.120–3.170). Conclusions Commercial motorcycle accidents have increased significantly over the past decade. There were statistical differences in severity based on EMR-ISS and the hospitalization in intensive care unit and death.